Distances covered by women soccer players during an official soccer game - Souglis, G. A.; Travlos, K. A.; Geladas, N.; Sotiropoulos, A. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The purpose of this study was to explore the distances covered by women soccer players during an official soccer game, as well as, the intensity with which the players covered the distance. Methods Twenty-one women soccer players [22.91±2.41 yrs; 20.1± 1.14%; and 7.62±2.20 yrs; for age, % body fat, and training experience, respectively] were separated in central defenders, full backs, central midfielders, wide midfielders and attackers. Distance covered during a match was measured in meters using personal wrist-worn devices with GPS and HR monitor (GARMIN 305 GPS, USA.). Total distance run & distance run at six different speed zones [walking (0-7.15 km/h), jogging (7.16-11.39 km/h), running (11.40-13.79 km/h), high-intensity running (13.80-19.31 km/h), very highintensity running (19.32-24.14 km/h) & sprinting (>24.15 km/h)] was measured for each player. Results & Discussion One way ANOVA for playing positions, revealed statistical significance for walking (F4,16 = 6.65, p< .001), jogging (F4,16 = 11.60, p< .001), running (F4,16 = 3.32, p< .05), high-speed running (F4,16 = 4.21, p< .02), and sprinting (F4,16 = 21.02, p< .001). Post hoc analyses indicated that: (a) for walking: wide midfielders (Ì = 2660.25±130.51) and central midfielders (Ì = 2619.40±116.89) covered greater distance than central defenders (Ì = 2361.50±105.38), (b) for jogging: (i) wide midfielders (Ì = 2721.00±129.83) covered greater distance than central midfielders (Ì = 2555.75±46.46), full-backs (Ì = 2495.60±27.39), attackers (Ì = 2541.25±61.08), and central defenders (Ì = 2389.00±55.08), and (ii) central midfielders than central defenders, (c) for highintensity running: wide midfielders (Ì = 1689.50±138.58) covered greater distance than central defenders (Ì = 1484.75±59.00), and (d) for sprinting: wide midfielders (Ì = 193.75±10.08) covered greater distance than full-backs (Ì = 165.60±8.91), attackers (Ì = 156.00±10.80) & central defenders (Ì = 140.00±6.63), and (ii) central midfielders (Ì = 173.75±6.29) and full-backs than central defenders. Conclusion The results suggest that wide midfielders cover greater distance in walking, jogging, high-intensity running, and sprinting zones compared with the other playing positions. The current findings provide useful information about high-intensity running and sprinting patterns during an official women soccer game, which may help coaches to develop specific physical fitness programs.